Pengaruh Konsumsi terhadap Inflasi di Indonesia - Daniel Ebenezer Silaban (Jurnal Syntax Admiration, 2025)
This study aims to analyze more deeply about the government's alignment with Micro, Small and Medium Enterprises (MSMEs) as an effort to recover the economy in the city of Medan as a result of the Covid-19 Pandemic. This study aims to see the extent of the development of MSMEs in Medan City during the Covid-19 pandemic, then analyze the policies implemented by the government and find solutions for the development of MSMEs during the pandemic. The method used in this research is qualitative research which is used to fully understand the reality of the government's alignment with Micro, Small and Medium Enterprises (MSMEs) as an effort to recover the economy of Medan City during the Covid-19 Pandemic. The results of the study show that the government's alignment with MSMEs during the pandemic can be seen from the policies taken both in the short and long term. The short-term policy is financial assistance in the form of soft loans or direct cash assistance. While the long-term strategy is focused on the introduction and use of digital technology for MSMEs as well as preparation for entering the Industry 4.0 era.